Screening of Antimicrobial Producing Bacteria from Berawe Beach Sand on Kampai Pangkalan Susu Island against Pathogenic Bacteria - Annisa, Rafika; Manalu, Kartika; Nasution, Rizki Amelia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Sand is naturally a place to live, grow and develop some marine animals and microorganisms, usually bacteria originating from the sea area that have a large number of bioactive compounds that can produce various kinds of secondary metabolites for further production of antimicrobials. The purpose of this study was to obtain bacteria that have the potential to produce antimicrobials and to characterize bacterial isolates on the sand of Berawe Beach, Kampai Island, Pangkalan Susu. In this study several stages were carried out, namely sampling, isolation, purification, morphological characterization, antimicrobial activity test, gram staining, biochemical test and determining the bacterial genus. The results of this study obtained 9 isolates (SP14A. SP15A, SP16A, SP24A, SP24B, SP35A, SP44A, SP44B and SP45A) which have the potential as antimicrobial producers. Characterization of antimicrobial bacterial isolates from the sand of Berawe Beach, Kampai Island, Pangkalan Susu, namely isolate SP14A, which is a gram- positive bacterium in the form of streptobacilli. SP15A, SP24B and SP44B isolates were coccus-shaped gram-positive bacteria. SP16A, SP35A, SP44A and SP45A isolates were gram-positive bacteria in the form of bacilli. And isolate SP24A is a gram-negative bacterium in the form of streptobacilli. All isolates produce catalase enzymes but do not use carbon and energy. Isolates that are motile (SP14A, SP15A, SP16A, SP24A, SP35A, SP44A and SP45A) can ferment glucose while non-motile (SP24B and SP44B) cannot ferment glucose. These bacteria come from the genera Bacillus, Micrococcus, LactoBacillus and Alcaligenes. Species of Bacillus pumilus, Bacillus subtilis, Bacillus firmus, LactoBacillus bulgaricus, Micrococcus luteus and Alcaligenes eutrophus.